The impact of tobacco excise revenue sharing (DBH CHT) on public health with the number of cigarettes smoked as a moderating variable in East Java Province - Nugroho, Edi; Harsoyo, Allamanda Titania; Ilyas, Guntoro; Dewi, Cynthia Atika; Siagian, Maria Florensia; Utomo, Rachmad (Educoretax, 2025)
This study aims to analyze the effect of Tobacco Excise Revenue Sharing Fund (DBH CHT) on public health in East Java Province with the number of cigarettes smoked as a moderating variable. One of the priorities in the allocation of DBH CHT is in the health sector, which is expected to increase the Public Health Index (IKM) with the right allocation. This study uses a quantitative method with secondary data sourced from the Directorate General of Fiscal Balance and the Central Statistics Agency covering the period 2019-2022. The hypothesis in this study was tested using the Multiple Linear Regression model for panel data. The results showed that DBH CHT had a positive and significant effect on IKM in East Java, while the number of cigarettes smoked did not significantly moderate the relationship. This shows that the allocation of DBH CHT is effective in improving public health, although cigarette consumption is still high. This study concludes that improving health facilities and programs funded by DBH CHT play an important role in improving public health, but controlling cigarette consumption is still a challenge.